P Filosofi Ungkapan Bereferensi Flora dan Fauna dalam Bahasa Aceh pada Masyarakat Gampong Pulo Kecamatan Syamtalira Aron - Rizka Fazila; Radhiah; Iba Harliyana (Global Action and Education for Society, 2026)
This research aims to study the forms, meanings, and philosophies contained in flora and fauna referenced expressions in the Acehnese language used by the community of Pulo village, Syamtalira Aron sub-district, North Aceh. The research describes the syntactic forms, examines the meanings contained within the flora and fauna referenced expressions, and analyzes the philosophy regarding the origin of the utterance of these expressions based on their meanings. This study uses descriptive qualitative research. The data was obtained through observation, interviews, documentation, recording techniques, and note-taking techniques. Based on the results of the research conducted by the researcher on the philosophy of flora and fauna referenced expressions in the Acehnese language among the community of Pulo village, Syamtalira Aron sub-district, North Aceh Regency, 50 data points were found in the form of expressions referencing flora and fauna, including 26 expressions referencing fauna (animals), 18 expressions referencing flora (plants), and 6 expressions referencing both flora and fauna simultaneously.